An experimental study on eccentrically braced beam-through steel frames with replaceable shear links. (1st March 2020) - Yao, Zucheng; Wang, Wei; Fang, Cheng; Zhang, Ziyao
Highlights: A modified eccentrically braced frame system is proposed for steel beam-through frames. Replaceable shear links are applied in this system. This system aims to achieve enhanced energy dissipation and effective seismic rehabilitation. Seven full-scale specimens are designed and tested. A comparative analysis on three testing parameters is conducted. Abstract: Prefabricated tension-only concentrically braced beam-through frames (BTFs) have received popularity for low-rise steel buildings in low to moderate seismic regions. However, the deteriorating pinched hysteretic behaviour of the tension-only concentric braces limits the energy dissipation capability of such systems under earthquakes. This study presents a modified eccentrically braced lateral force-resisting system aiming to enhance the energy dissipation capability of the BTFs. Meanwhile, seismic resilience is promoted with the utilization of replaceable shear link beams acting as structural fuses. The structural configuration and the basic design concept of the proposed eccentrically braced BTFs is first introduced. The essential mechanical characteristics of this bracing system are subsequently described with a simplified theoretical model. Seven full-scale eccentrically braced BTF specimens are subsequently tested, where the effects of link length, bracing angle, and link section are examined. The test results show that short links tend to improve the stiffness, load resistance and ductility of the BTF due to the exhibited shear-dominant behaviour. An increase in bracing angle leads to increased lateral stiffness and load resistance but at the cost of reduced ductility. Reducing the link section helps delay the development of weld cracks and results in better ductility of the structural fuse. The test results also warn that weld defects and inappropriate design of the link beam would induce brittle weld fractures at the ends of the link and lead to unsatisfactory ductility.